Preventive treatment can reverse cognitive impairment in chronic migraine - Cristina González-Mingot; Anna Gil-Sánchez; Marc Canudes-Solans; Silvia Peralta-Moncusi; Maria José Solana-Moga; Luis Brieva-Ruiz (The Journal of Headache and Pain, 2022)
Abstract Objective To study the impact of chronic migraine (CM) on the cognition and quality of life (QoL) of patients in the interictal period, and to analyse the degree of reversibility of any observed alterations following the use of preventive treatment. Background CM is a highly disabling disease, and migraineurs often have associated comorbidities, such as subjective memory problems, that are involved in the development of cognitive impairment. Our hypotheses are that patients suffering from chronic migraine experience objective cognitive alterations that are not only due to the pain that they suffer or their current emotional state. Furthermore, preventive treatment should be capable of reversing, or at least reducing, the impact of CM on the cognition and QoL of migraineurs. Methods The cognition and QoL of 50 control subjects and 46 patients with CM were assessed using a battery of tests, prior to the use of preventive treatment based on botulinum toxin or oral drugs and after 3 months of this treatment. Results Compared with controls, patients with CM had lower scores on the assessment of cognitive performance (Rey-Osterrieth Complex Figure test [ROCF] (p<0.05), Trail Making Test [TMT] B) (p < 0.05) and QoL (p < 0.05). Three months after the use of preventive treatment, improvement was observed in all cognitive parameters (p < 0.05) and QoL (p < 0.05), except the ROCF copy task (p = 0.79). No statistically significant differences were observed when these outcomes were compared based on treatment. Conclusions This study confirms poor cognitive performance that is not explained by migraine pain itself, as it occurs in the interictal period, irrespective of the patient’s emotional status. Our findings show that these effects are reversible in some cases with preventive treatment of CM, reaffirming the important impact of this condition on the QoL of these patients, and the need to establish preventive treatment guidelines.